PARAMETERS DETERMINING THE DEGREE OF THE REQUIRED EXTERNAL TRANSVERSAL FRP REINFORCEMENT OF METAL CYLINDRICAL TANKS (Collection of scientific works «Modern structures of metal and wood», 2022)
The main reasons for the wear of the walls of metal cylindrical tanks are corrosion and fatigue of the metal of their vertical joints. It is possible to replenish for the corrosion losses of the material, as well as to reduce the level of acting stresses to values allowed by the conditions of metal fatigue, with external transverse reinforcement with fiber reinforced plastic (FRP). Sequential consideration of the operation of steel shells of cylindrical tanks reinforced with external transverse FRP reinforcement allows to obtain the values of the corresponding hoop stresses. The necessary limitation of the values of the maximum stresses of the metal components makes it possible to determine the coefficients of the external FRP reinforcement of these structures. Herewith the analysis of the obtained theoretical results indicates the mandatory need to take into account the temperature  deformations  of  structural  elements  that  exhibit  different  temperature-deformation properties, as well as a significant impact on the results obtained by the longitudinal deformations of the metal shells of these structures. The calculation methods proposed in the article make it possible to determine the necessary parameters  for  strengthening  the  bodies  of  metal  cylindrical  tanks  with  an  external  transversely directed FRP reinforcement that perceives the actions of ring forces. The main factors determining the effectiveness of the obtained solutions are the residual strength of the material of the metal shells of the tanks, as well as the modulus of elasticity of the used FRP. The theoretical expediency of the effective use of low-modulus FRP is confirmed for structures with high strength indicators of metal bases, and high-modulus – in cases of significant limitation of the stress level of metal elements.